Предмет: Алгебра,
автор: shuk26082018
2(х – 1) – 5х(3х – 1)
shuk26082018:
3. Виконайте множення многочлена на многочлен: (х – 1)(х + 2)
Ответы
Автор ответа:
1
Ответ:
2(х – 1) – 5х(3х – 1) = 2х - 2 - 15х^2 + 5х = 7х - 15х^2 - 2
Автор ответа:
0
Ответ:
7х - 2 - 15
Объяснение:
2(х-1) - 5х(3х-1) = 2x - 2 -15 + 5x = 7x - 2 - 15
Похожие вопросы
Предмет: Русский язык,
автор: смиимс
Предмет: Алгебра,
автор: Nastyawn
Предмет: Математика,
автор: ruzanovasofya
Предмет: Математика,
автор: kristinapanarina2
Предмет: Химия,
автор: LesyaArtisyk666777